Terapi Psikososial Sebagai Strategi Meningkatkan Resiliensi Pada Remaja Penyandang Disabilitas Tuna Daksa - Athaya Nursabrina; Muhammad Sultan Alrahman; Revala Utami Yuniar; Salsabila Damar Mulya; Ati Kusmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In Indonesia, there are approximately 22.97 million people, or approximately 8.5 percent of the population, with the largest proportion being in the elderly group. One form of disability is physical disability, a condition in which limbs are imperfect due to defects that cause damage to bones, muscles, and joints, so that body functions cannot run normally. This condition often impacts not only the physical aspect, but also the psychological health of the sufferer. One of the main challenges faced by people with physical disabilities is maintaining resilience, namely the individual's ability to overcome depression, anxiety, pressure, and stress in living daily life. This study uses a literature review method to examine the results of previous studies relevant to the topic of resilience in people with physical disabilities. The data collection process was carried out through literature searches on the internet using sources from Google Scholar and Google Books. The criteria for selected literature include research that focuses on psychological interventions, especially reality therapy, and its effect on increasing resilience. Reality therapy is a counseling approach that emphasizes personal responsibility, awareness of choices, and the development of skills to face life's challenges effectively. The study results indicate that reality therapy has been shown to have a positive effect on increasing resilience in individuals with physical disabilities. Through a structured counseling process, this therapy helps individuals recognize their potential, develop positive attitudes, and develop adaptive coping strategies. Furthermore, reality therapy can increase motivation, self-confidence, and the ability to make constructive decisions when faced with physical limitations and social pressures. These findings indicate that the application of reality therapy can be an effective approach to supporting the psychological well-being of individuals with physical disabilities, while also contributing to more holistic rehabilitation efforts in Indonesia.